Improving Student Learning Outcomes Through the Probing Prompting Learning Model on Trigonometric Ratios in Right-Angled Triangles in Class X-MPLB-A at SMK Negeri 1 Suwawa - Daluta, Alpin; Machmud, Tedy; A. Y. Pauweni, Khardiyawan (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2024)
This classroom action research aims to improve student learning outcomes on trigonometric ratios in right-angled triangles using the probing prompting learning model. This study is a classroom action research conducted at SMK Negeri 1 Suwawa during the even semester of the 2022/2023 academic year. The research involved 20 students and a teacher as subjects. The instruments used included teacher observation sheets, student observation sheets, and learning outcome tests. The research was conducted over 2 cycles. The results showed that the teacher's activity observations, which reached good and very good categories, increased from 80.94% to 80.95%. Similarly, the student observations that reached good and very good categories also increased from 74.99% to 79.16%. Student learning outcomes improved from 80% to 90%. All assessment aspects met the learning success indicators in the second cycle through the application of the probing prompting learning model. Based on this research, there are benefits to applying the probing prompting learning model, as it can enhance students' mathematics learning outcomes and improve their comprehension of mathematics.